Emergent scientist (EDP Sciences, 2017)
Emergent Scientist is an open access international scientific journal dedicated to a student authorship and readership, and to lesser extent to teachers and researchers. Emergent Scientist is intended to provide students with accessible scientific material and to offer them a first publishing experience. For senior scientists, Emergent Scientist can be used to provide teaching material and can constitute an introduction to questions out of the reader's area of expertise.